DE MACROCARPAEAE GRISEBACH (EX GENTIANACEIS) SPECIEBUS NOVIS V: TWENTY-THREE NEW SPECIES LARGELY FROM PERU, AND TYPIFICATION OF ALL SPECIES IN THE GENUS - Grant, Jason (My University, 2004)
In preparation for a monograph of Macrocarpaea (Gentianaceae: Helieae), 23 new species are here described and illustrated: 1 from Colombia (M. biremis), 3 from Ecuador (M. elix, M. gattaca, and M. pringleana), and 19 from Peru (M. canoëfolia, M. dillonii, M. ericii, M. fortisiana, M. innarrabilis, M. jalca, M. kayakifolia, M. kuelap, M. kuepferiana, M. luya, M. normae, M. obnubilata, M. ostentans, M. pajonalis, M. robin-fosteri, M. tabula-fluctivagifolia, M. tahuantinsuyuana, M. wallnoeferi, and M. weigendiorum). A list of all names originally described in, or transferred to, Macrocarpaea as of year 2002 is presented. Lectotypes are selected for 12 taxa as follows: Lisianthus obtusifolius var. constrictus Griseb., Macrocarpaea bangiana Gilg, M. bogotana Gilg, M. calophylla Gilg, M. chlorantha Gilg, M. cochabambensis Gilg-Ben., M. glaziovii Gilg, M. hartii Krug & Urb., M. micrantha Gilg, M. pachyphylla Gilg, M. polyantha Gilg, and M. rubra Malme. A neotype is selected for M. duquei Gilg-Ben., and M. weberbaueri Gilg is excluded from use.
Keywords: Gentianaceae; Helieae; Macrocarpaea; morphology; Neotropics